Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/sla.0b013e31821d4a2d
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Management and Chronic Pain After Open Inguinal Hernia Repair

Abstract: Mesh contact with a nerve removed from its natural bed may cause chronic long-term pain. The combination of IIN neurolysis and the Lichtenstein repair should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
82
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 40 publications
6
82
0
14
Order By: Relevance
“…This series has given some clarity to the issue of nerve mobilization, clearly demonstrating that this should be avoided. The first main conclusion of Reinpold's article is ''The nerves should always be visualized, and handled with care [9]. '' We hope that the conclusion that ''nerve identification had no influence on persistent pain'' is not taken out of the context of this study promoting careless nerve handling, leading to patient disability and surgeon liability.…”
Section: Dear Editorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This series has given some clarity to the issue of nerve mobilization, clearly demonstrating that this should be avoided. The first main conclusion of Reinpold's article is ''The nerves should always be visualized, and handled with care [9]. '' We hope that the conclusion that ''nerve identification had no influence on persistent pain'' is not taken out of the context of this study promoting careless nerve handling, leading to patient disability and surgeon liability.…”
Section: Dear Editorsmentioning
confidence: 95%
“…Importantly, the authors comment that such a comparison with a ''group with no nerve identification would be somewhat unethical based on previous literature.'' In regard to the citation in the discussion that Reinpold's article of long-term 5-year data of nerve management and rates of chronic pain ''suggest[s] that other factors rather than nerve identification are important,'' the conclusions from that study are not directly comparable [9]. This longitudinal series did not specifically focus on defining the role of nerve identification with the IIN, IHN, and GB identified in only 88.0, 45.3, and 38.2 % of the cases, respectively.…”
Section: Dear Editorsmentioning
confidence: 99%
“…(8) In a study, the rates of chronic pain after 6 months and 5 years were 16.5% and 16.1%, respectively. (29) Ravichandran D et al evaluated the differences in the incidence of pain between the ilioinguinal nerve 'preserved' and 'divided' sides and did not find any significant difference in the pain between both sides. He found that at 6 months postoperatively, pain was present in 5% patients on the nerve preserved side versus 0% on the nerve division side.…”
Section: Discussionmentioning
confidence: 99%
“…The Reinpold study [17] has now shown that mobilization of the ilioinguinal nerve during open repair causes short term and long term pain with data extending out to ten years. In patients with chronic postherniorrhaphy pain the patient's reoperation to alleviate that pain many times shows evidence of direct injury from suture, tacks, and mesh contraction [18].…”
Section: Discussionmentioning
confidence: 99%